Sovereignty and Cyber Security: Re-Thinking State Power in the 21st Century - Nawazish Ali; Afzaal Ahmad; Iqra Zafar (Indus Journal of Social Sciences, 2025)
The relationship between cyber security and state sovereignty has become a very important aspect of international politics in the 21 st century. The borderlessness of cyberspace is slowly eroding traditional ideas of territorial control and political authority as threats like these can now be made through cyberspace. Because cyber-attacks, web-based spying, and manipulation of information are beyond national borders. This paper discusses how states are re-examining the exercise of power in the digital age and balancing the requirements of the security, rule and civil liberties. It examines the changing paradigms of cyber sovereignty, how cyber capabilities can be strategically used in offence and defence and impact international law and diplomacy. The paper argues that cybersecurity is not simply a technical concern, but a central element of state power that requires innovative policy approaches and multilateral cooperation to safeguard national interests in an increasingly interconnected world.